2022
DOI: 10.3390/jpm12060994
|View full text |Cite
|
Sign up to set email alerts
|

Serological Response and Relationship with Gender-Sensitive Variables among Healthcare Workers after SARS-CoV-2 Vaccination

Abstract: Vaccine-induced immunity is a key strategy in the long-term control of the COVID-19 pandemic. The aim of our study was to explore the relationship between mRNA vaccine-induced antibodies and gender-sensitive variables among healthcare workers. Two thousand-sixty-five volunteers who received the BNT162b2 vaccine were enrolled in the study and followed up. Demographic, clinical, and social variables (educational level, marital status, occupation, childcare) were evaluated through a self-administered questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…According to our findings, the IgG titers were inversely related to age in both sexes. This finding is almost universal and common in other studies, too [ 25 , 27 , 28 , 29 , 31 ]. Older people develop lower IgG titers, and this is consistent with higher vulnerability to COVID-19 and other infections as well [ 1 , 2 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…According to our findings, the IgG titers were inversely related to age in both sexes. This finding is almost universal and common in other studies, too [ 25 , 27 , 28 , 29 , 31 ]. Older people develop lower IgG titers, and this is consistent with higher vulnerability to COVID-19 and other infections as well [ 1 , 2 ].…”
Section: Discussionsupporting
confidence: 80%
“…In our study, women developed higher IgG titers than men, and this difference was statistically significant. Although there are some studies supporting the contrary observation that men developed higher IgG titers than women [ 25 ] or that women developed insignificantly higher IgG titers than men [ 26 ], most studies found that females tend to produce higher titers than males [ 27 , 28 , 29 , 30 , 31 ]. This finding is in accordance with the generally accepted view about sex-based immunological differences that contributed to higher morbidity and mortality in men due to COVID-19 infection as well [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…As with other studies, we found that age and male sex were two anthropological factors for the hypo-responsiveness to COVID-19 vaccination [ 24 – 26 ]. Another study interestingly showed that married and divorced males, but not singles and cohabitants, had a significantly lower SARS-CoV-2 IgG titer than females [ 27 ]. It has been postulated that estrogen, interacting with ESR1/2 receptors may potentially inhibit SARS-CoV-2 related immune response signaling in host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Only questionnaires were employed and the timeframe for self-reported symptoms was restricted to seven days after vaccination in subjects without previous COVID-19 infection. Nevertheless, in a large study, Cangemi et al [ 25 ] reported that the anti-Spike IgG were inversely associated with age, and a reduction of more than 82% was directly associated with male sex.…”
Section: Discussionmentioning
confidence: 99%